Cho hai biểu thức:
\(\begin{array}{l}A=3 \sqrt{7}-\sqrt{28}+\sqrt{175}-3 \\B=\frac{x-\sqrt{x}}{\sqrt{x}}+\frac{x+\sqrt{x}}{\sqrt{x}+1}(\text { với } x\gt 0 \text { ). }\end{array}\)a) Rút gọn biểu thức \(A\) và biểu thức \(B\).
Giải thích:
\(\begin{array}{l}A=3 \sqrt{7}-\sqrt{28}+\sqrt{175}-3 \\ =3 \sqrt{7}-2 \sqrt{7}+5 \sqrt{7}-3 \\ =6 \sqrt{7}-3\end{array}\)
\(\begin{array}{l}\text { Với } x\gt 0 \text { ta có: } \\ B=\frac{x-\sqrt{x}}{\sqrt{x}}+\frac{x+\sqrt{x}}{\sqrt{x}+1}=\frac{\sqrt{x}(\sqrt{x}-1)}{\sqrt{x}}+\frac{\sqrt{x}(\sqrt{x}+1)}{\sqrt{x}+1} \\ \sqrt{x}-1+\sqrt{x}=2 \sqrt{x}-1 .\end{array}\)
Câu hỏi này nằm trong: